2021
DOI: 10.1161/circresaha.121.319066
|View full text |Cite
|
Sign up to set email alerts
|

FAK Activation Promotes SMC Dedifferentiation via Increased DNA Methylation in Contractile Genes

Abstract: Rationale: Vascular smooth muscle cells (SMCs) exhibit remarkable plasticity and can undergo dedifferentiation upon pathological stimuli associated with disease and interventions. Objective: Although epigenetic changes are critical in SMC phenotype switching, a fundamental regulator that governs the epigenetic machineries regulating the fate of SMC phenotype has not been elucidated. Methods and Results: Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Furthermore, Jeong et al discovered that FAK, which is induced upon vascular injury, elicits VSMC dedifferentiation by stabilizing DNMT3A. They further show that FAK inhibition leads to DNMT3A degradation and DNA hypomethylation of contractile gene promoters, which increased VSMC contractile protein expression ( Jeong et al, 2021 ).…”
Section: Vascular Smooth Muscle Cellsmentioning
confidence: 99%
“…Furthermore, Jeong et al discovered that FAK, which is induced upon vascular injury, elicits VSMC dedifferentiation by stabilizing DNMT3A. They further show that FAK inhibition leads to DNMT3A degradation and DNA hypomethylation of contractile gene promoters, which increased VSMC contractile protein expression ( Jeong et al, 2021 ).…”
Section: Vascular Smooth Muscle Cellsmentioning
confidence: 99%
“…IF assays further confirmed that CENPF deficiency significantly restricted FAK in the nucleus (Figure 7H). Based on the report that PND-1186 is an inhibitor of FAK and that it can restrict FAK in the nucleus and inhibit its activity [32], we verified that PND-1186 could repress the activation of FAK and block FAK in the nucleus in GC cells (Supplementary Figure S4A-B). Finally, the effect of CENPF overexpression on the MAPK signaling pathway could be restored by PND-1186 in HGC27 and AGS cells (Figure 7I).…”
Section: Cenpf Activated the Mapk Signaling Pathway By Promoting Fak ...mentioning
confidence: 60%
“…Abbreviations: IP, immunoprecipitation; MS, mass spectrometry; IF, immunofluorescence; CENPF, centromere protein F; FAK, focal adhesion kinase; DMSO, dimethyl sulfoxide; H3, histone 3; Erk1/2, extracellular signal-regulated kinase 1/2; Elk1, ETS-like gene 1; SD, standard deviation. its activity [32], a molecular mechanism by which CENPF activates the MAPK signaling pathway by promoting FAK entry into the cytoplasm was elucidated. This is the first report on the regulatory relationship between CENPF and FAK.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced DNMT3A protein leads to DNA hypomethylation in contractile gene promoters, which increased SMC contractile protein expression. DNMT3A degradation via E3 ligase TRAF6 drives differentiation of SMCs ( Jeong et al, 2021 ). A unifying epigenetic mechanism also has been proposed that confers reversible SMC differentiation governed by the DNA-modifying enzyme ten-eleven translocation-2 (TET2).…”
Section: The Growth Factors That Influence Tumor Integrin Function In...mentioning
confidence: 99%